Pengembangangan Media Pembelajaran IPS Berbasis Game Edukasi Digital Wordwall untuk Meningkatkan Hasil Belajar Siswa Kelas 9 di MTS Tsamrotul Huda Kecapi Jepara - Kholisoh, Siti Nor; Ariyanti, Vega; Setyani, Dewi; Dany Miftaf M. Nur (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to develop educational game-based learning media using Wordwall for the subject of social and cultural change and globalization for 9C grade students. The research objectives include: 1) Describing the development procedure of educational game-based learning media using Wordwall in teaching social and cultural change and globalization at MTs Tsamrotul Huda 9C grade, 2) Assessing the feasibility of this learning media, and 3) Measuring the effectiveness of this learning media in teaching the related material. This study adopts the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The results of media validation showed a feasibility percentage of 89.3%, while material validation achieved 88%. The media trial was conducted with 9C grade students using a questionnaire, resulting in a feasibility level of 83.5%. Based on validation and trial results, the Wordwall educational game-based learning media is deemed feasible and effective for use in teaching the subject of social and cultural change and globalization at MTs Tsamrotul Huda Kecapi Jepara. This abstract provides a general overview of the study and the content of the article.